Antecedents and consequences affecting job plateau among school employees in Tehran - Nafiseh Ghasemi Zargar; parivash jafari; Nadergholi Ghourchian; AmirHossein Mohammaddavoudi (مدیریت و چشم انداز آموزش)
AbstractThe purpose of the present study is to investigate the antecedents and consequences of job burnout among school employees in Tehran. According to its purpose, the research method is applicable, pragmatic in terms of paradigm, and qualitative in terms of method, with a content analysis approach and with the aim of reducing it. The statistical population of the research consists of 15 education experts who include members of officials with experience in education in Tehran, selected for sample selection using the purposeful sampling method, and the sampling process continued until theoretical saturation was reached. Data collection is through semi-structured interviews. Data analysis was done using thematic analysis method and MAXQDA 18 software. Data analysis is done in order to understand the facts and concepts of the research. According to the use of content analysis method in the present research, the components and antecedents resulting from the systematic review and the components and factors resulting from the interviews conducted in the form of a combination of all factors was presented as a model for reducing job burnout among school employees in Tehran with the qualitative approach of content analysis. The results showed that the incidence of job plateauing in schools consists of 11 effective factors, including school policies and education system, inefficient management, inappropriate reward and promotion system, unfavorable evaluation system, unhealthy interactions among colleagues, lack of organizational dynamics, financial issues, inappropriate structure and laws, individual characteristics, social and economic conditions, job characteristics and individual consequences; and they should be focused on in order to reduce job plateauing.Extended abstractIntroductionResearches have shown that employees who are progressing in the right career path in the organization work with more motivation, have more role and extra-role performance, are more satisfied, and the tendency to leave the organization and absenteeism are less observed in them. For this reason, organizations are always looking for effective solutions to manage the career paths of employees (Fayazi & Ziyaei, 2014). The phenomenon of career plateauing describes a stage of work in which a person is less likely to receive a formal promotion or face fewer job challenges in their career. The plateau may be called a silent crisis, a slow fall and a continuous and silent destruction. Job plateau as a mental health issue has appeared in organizations that see their members in a job position for a long time without promotion or change of position (Damghanian & Shahbaz, 2019).Plateau is a feeling of disappointment and psychological failure that employees experience after a temporary or permanent stop in the path of career development. This feeling occurs when the organization does not have jobs at high management levels, or when an employee's abilities do not match the job requirements, which are normally on his career path, and therefore the employee decides not to seek further advancement (Abdulvand & Zakeri, 2018). Unmotivated employees are an obstacle in the advancement of the organization's goals and have a brake on the progress and achievement of organizational goals and excellence. Many researchers in the organizational profession believe that job burnout is quickly becoming a critical managerial and organizational issue that needs to be properly managed to prevent employee dissatisfaction (Noah Pisheh, 2018).Therefore, in this research, we are looking for an answer to this question: what are the antecedents and consequences of job plateauing among school employees in Tehran?Theoretical frameworkPlateauThe word "plateau" in geological topics means a high path in a flat land. Researchers have used this word in the category of management science and have used it to express a series of situations that appear in the human resources of organizations. They believe that the plateau in the professional and career path indicates stagnation, lack of progress and reduction of individual learning, and induces a feeling of depression and failure. It should be noted that the career plateau has a general structure related to some work results. The emergence of job plateau is a problem that employees, managers and organizations should try to solve (Iranzade et al, 2021). Career plateau is defined as a point of job and career where the probability of additional hierarchical promotion is very low. Due to changes in organizational environments, one of the most important issues related to career paths in the next decade is career plateauing (Chou et al, 2022). A plateau is a point in a person's job and organizational career where progress and improvement (in other words, promotion) is impossible. This is a relatively old concept studied by various researchers. There are different types of plateaus. First, we can distinguish between two levels of job plateauing: structural plateauing (hierarchical plateauing), and content plateauing (Huaman & Lahlouh, 2022).Jin et al, (2023) investigated the role of career age and career plateau in the relationship between ethical leadership and knowledge sharing. Seniority and career plateau affect moral leadership and knowledge sharing among employees.Elsayed & Abd-Elmonem (2023) investigated the relationship between nursing staff's understanding of job burnout and job enthusiasm. The results showed that nursing staff's understanding of job plateauing has a significant relationship with their job enthusiasm.Research methodologyThe research method is applicable in terms of its purpose, pragmatic in terms of paradigm, and qualitative in terms of method, with a content analysis approach and with the aim of reducing it. The statistical population of the research consists of 15 education experts who include members of officials with experience in education in Tehran, selected for sample selection using the purposeful sampling method, and the sampling process continued until theoretical saturation was reached. Data collection is through semi-structured interviews.Research findingsData analysis was done using thematic analysis method and MAXQDA 18 software. Data analysis is done in order to understand the facts and concepts of the research. According to the use of content analysis method in the present research, the components and antecedents resulting from the systematic review and the components and factors resulting from the interviews conducted in the form of a combination of all factors was presented as a model for reducing job burnout among school employees in Tehran with the qualitative approach of content analysis. The results showed that the incidence of job plateauing in schools consists of 11 effective factors, including school policies and education system, inefficient management, inappropriate reward and promotion system, unfavorable evaluation system, unhealthy interactions among colleagues, lack of organizational dynamics, financial issues, inappropriate structure and laws, individual characteristics, social and economic conditions, job characteristics and individual consequences; and they should be focused on in order to reduce job plateauing.ConclusionThe present study was conducted with the aim of investigating the antecedents and consequences of job burnout among school employees in Tehran. The results of this research correspond with the results of Zeinabadi et al, (2022), Paryar et al, (2022), Naghiloo et al, (2022), Farjam et al, (2022), Iranzadeh et al, (2021), Jin et al, (2023), Elsayed & Abd-Elmonem (2023), Darling & Cunningham (2023), DiRenzo et al, (2022), Huaman & Lahlouh (2022), Changya et al, (2022), and Jing et al, (2022). Changya et al, (2022) showed that there are positive relationships between previous potential factors (job compatibility, person-environment fit, psychological capital and workplace support). Job burnout was positively related to counterproductive work behavior, job insecurity, rational psychological distress, and intention to quit; but negatively related to job satisfaction, extra-role performance, intra-role performance, job involvement, job satisfaction, coaching support, organizational commitment, and commitment. Also, job plateauing was related to other variables, including age, gender, job history, race, and role ambiguity.Based on the research results, the following suggestions are presented:1- Considering the importance of education and awareness, school administrators should set up workshops according to the needs and methods of the day based on the development of employees and put targeted and continuous training programs in the executive agenda of their organization.2- Paying attention, recognizing and appreciating the small and big successes of employees will have a positive effect on the work process ahead of them. School managers should pay attention to the efforts and performances of the employees and improve their reward and payment system based on the performances of the employees.